Antenatal couples’ counselling in Uganda (ACCU): study protocol for a randomised controlled feasibility trial - Mubangizi, Vincent; McGrath, Nuala; Kabakyenga, Jerome Kahuma; Muller, Ingrid; Stuart, Beth L.; Raftery, James P.; Natukunda, Sylvia; Ngonzi, Joseph; Goodhart, Clare; Willcox, Merlin Luke (Pilot and Feasibility Studies, 2022)
Background: Common avoidable factors leading to maternal, perinatal and neonatal deaths include lack of birth planning (and delivery in an inappropriate place) and unmet need for contraception. Progress has been slow because routine antenatal care has focused only on women. Yet, in Uganda, many women first want the approval of their husbands. The World Health Organization recommends postpartum family planning (PPFP) as a critical component of health care. The aim of this trial is to test the feasibility of recruiting and retaining participants in a trial of a complex community-based intervention to provide counselling to antenatal couples in Uganda. Methods: This is a two-group, non-blinded cluster-randomised controlled feasibility trial of a complex intervention. Primary health centres in Uganda will be randomised to receive the intervention or usual care provided by the Ministry of Health. The intervention consists of training village health teams to provide basic counselling to couples at home, encouraging men to accompany their wives to an antenatal clinic, and secondly of training health workers to provide information and counselling to couples at antenatal clinics, to facilitate shared decision-making on the most appropriate place of delivery, and postpartum contraception. We aim to recruit 2 health centres in each arm, each with 10 village health teams, each of whom will aim to recruit 35 pregnant women (a total of 700 women per arm). The village health teams will follow up and collect data on pregnant women in the community up to 12 months after delivery and will directly enter the data using the COSMOS software on a smartphone. Discussion: This intervention addresses two key avoidable factors in maternal, perinatal and neonatal deaths (lack of family planning and inappropriate place of delivery). Determining the acceptability and feasibility of antenatal couples’ counselling in this study will inform the design of a fully randomised controlled clinical trial. If this trial demonstrates the feasibility of recruitment and delivery, we will seek funding to conduct a fully powered trial of the complex intervention for improving uptake of birth planning and postpartum family planning in Uganda.
Keywords: Antenatal; Film; Contraception; Family planning; Postpartum; Couples counselling; Birth preparedness; Birth planning; Uganda